Loss of the oxygen sensor PHD3 enhances the innate immune response to abdominal sepsis - Kiss, Judit; Mollenhauer, Martin; Kirchberg, Johanna; Radhakrishnan, Praveen; Niemietz, Thomas; Dudda, Johanna Lena; Steinert, Gunnar; Weitz, Jürgen; Schneider, Martin (The journal of immunology, 2012)
Hypoxia and HIFs (HIF-1α and HIF-2α) modulate innate immune responses in the setting of systemic inflammatory responses and sepsis. The HIF prolyl hydroxylase enzymes PHD1, PHD2 and PHD3 regulate the mammalian adaptive response to hypoxia; however, their significance in the innate immune response has not been elucidated. We demonstrate in this study that deficiency of PHD3 (PHD3−/−) specifically shortens the survival of mice subjected to various models of abdominal sepsis because of an overwhelming innate immune response, leading to premature organ dysfunction. By contrast, this phenotype was absent in mice deficient for PHD1 (PHD1−/−) or PHD2 (PHD2+/−). In vivo, plasma levels of proinflammatory cytokines were enhanced, and recruitment of macrophages to internal organs was increased in septic PHD3-deficient mice. Reciprocal bone marrow transplantation in sublethally irradiated mice revealed that enhanced susceptibility of PHD3-deficient mice to sepsis-related lethality was specifically caused by loss of PHD3 in myeloid cells. Several in vitro assays revealed enhanced cytokine production, migration, phagocytic capacity, and proinflammatory activation of PHD3-deficient macrophages. Increased proinflammatory activity of PHD3-deficient macrophages occurred concomitantly with enhanced HIF-1α protein stabilization and increased NF-κB activity, and interference with the expression of HIF-1α or the canonical NF-κB pathway blunted their proinflammatory phenotype. It is concluded that impairment of PHD3 enzyme function aggravates the clinical course of abdominal sepsis via HIF-1α- and NF-κB-mediated enhancement of the innate immune response.
Gesehen am 04.02.2019